Sistem Informasi UKM Futsal STMIK IKMI Cirebon Berbasis WEB Menggunakan Metode Waterfall - Achmad Baihaqi; Nana Suarna; Dita Amalia Rizki (INTERNAL (Information System Journal), 2022)
Information about an Organination or a Student Activity Unit is very important to inform the activities carried out by an organization or Student Activity Unit, such as the Futsal STMIK IKMI Cirebon Student Activity Unit. The process of managing the administration of members who are still manual, providing information that has not been  and the absence of archives of the activities that have been carried out make the Futsal Student Activity Unit at STMIK IKMI Cirebon unable to recap activities. This is a factor in the futsal student activity unit's problems in member data and activity archives. This research will create a system that can accommodate existing problems. This research uses the waterfall method to develop the system. The system created will later use the website as a medium. This research method was chosen because it is a simple process and also easy to apply. The stages in this waterfall method include Needs Analysis, System Design, Workmanship, Verification, and Maintenance. The system created will improve student services and make it easier for futsal student activity unit administrators to convey information and make it easier for members to obtain information.